Multiple breath nitrogen washout: a feasible alternative to mass spectrometry. - Renee Jensen (Public Library of Science (PLoS), 2013)
Background The lung clearance index (LCI), measured by multiple breath washout (MBW), reflects global ventilation inhomogeneity and is a sensitive marker of early cystic fibrosis (CF) lung disease. Current evidence is based on a customized mass spectrometry system that uses sulfur hexafluoride (SF6) as a tracer gas, which is not widely available. Nitrogen (N2) washout may be better suited for clinical use and multi-center trials. Objective To compare the results obtained from a N2 washout system to those generated by the SF6 based system in healthy children and children with CF. Methods Children with CF were recruited from outpatient clinics; healthy children were recruited from the Research4Kids online portal. Participants performed MBWSF6 (Amis 2000, Innovision, Denmark) and MBWN2 (ExhalyzerD, EcoMedics, Switzerland) in triplicate, in random order on the same day. Agreement between systems was assessed by Bland-Altman plot. Results Sixty-two healthy and 61 children with CF completed measurements on both systems. In health there was good agreement between systems (limits of agreement -0.7 to 1.9); on average N2 produced higher values of LCI (mean difference 0.58 (95% CI 0.42 to 0.74)). In CF the difference between systems was double that in health with a clear bias towards disproportionately higher LCIN2 compared to LCISF6 at higher mean values of LCI. Conclusion LCIN2 and LCISF6 have similar discriminative power and intra-session repeatability but are not interchangeable. MBWN2 offers a valid new tool to investigate early obstructive lung disease in CF, but requires independent normative values.